ЕМКОСТЬ СРЕДЫ — СОДЕРЖАНИЕ ПОНЯТИЯ И ЕГО ПРИМЕНЕНИЕ В ЭКОЛОГИИ - (:unkn) unknown (Киев : Наукова думка, 1981)
Обоснована полезность термина «емкость среды» для различных разделов экологии. Предложено определение понятия. Рассмотрены показатели емкости среды и требования к исследованиям в этой области.
Environment capacity: the content of the notion and its application in ecology
The applicability of the notion "environment capacity" is substantiated for different branches of ecology. The definition of the notion is suggested. The indices of the environment capacity and requirements to research in this field are considered.